Žinių kultūros ugdymas – strateginė akademinių bibliotekų valdymo kryptis - Pupelienė, Janina (Information & Media, 2007)
Akademinës bibliotekos, aktyviai dalyvaujanèios universitetiniø þiniø kûrimo ir ypaè sklaidos procesuose, yra stipriai veikiamos palyginti uþdaros akademinës aplinkos su jai bûdinga institucine autonomija ir vertybëmis, daþnai prieðingomis efektyvaus dalijimosi þiniomis kultûrai. Akademinës bibliotekos turi ieðkoti bûdø, kaip tapti atviromis, nauja darbo kultûra pasiþyminèiomis organizacijomis, kurti veiklos strategijas, kuriø ágyvendinimo sëkmæ daþnai lemia organizacijos vidinë kultûra. Dalijimosi þiniomis kultûra straipsnyje nagrinëjama kaip organizacijos bendros kultûros dalis. Aptariami galimi organizaciniai ir techniniai dalijimosi þiniomis metodai, ypaè pabrëþiant pasitikëjimo ir tarpusavio supratimo aplinkos kûrimà. Pagrindinis straipsnio tikslas – atlikti þiniø kultûros ugdymo organizacijose moksliniø publikacijø analizæ, tuo atkreipti Lietuvos bibliotekø vadovø dëmesá á ðià aktualià valdymo problemà ir paskatinti juos ugdyti savo vadovaujamose organizacijose tokià kultûrà. Atliekant tyrimà naudotasi mokslinës literatûros analizës metodu*.Development of knowledge culture – a strategic direction for the management of academic librariesJanina PupelienėSummaryOver the last decade there is a continuing discussion on various aspects of modern organization in the management literature. The constant development of the individual’s skills and knowledge is being recognised as an important element of organization’s capacity to realise changes. Knowledge sharing is being treated as critical to organizations that use their knowledge as an asset to achieve competitive advantage. Academic libraries, being traditionally defined as information and knowledge related organizations, are being influenced by this discussion as well. These libraries have to develop a new strategy to correspond to this new working environment. From the point of management, Lithuanian academic libraries could be described as traditional and not very conductive to the knowledge sharing culture. In the article, this assumption is illustrated by some findings revealed by students of the Faculty of Communication of Vilnius University. From the author’s point of view, it is useful for the managers of Lithuanian academic libraries to be acquainted with the theoretical and practical ideas of the development of knowledge culture in organizations. The main purpose of this article is to review some latest publications on the development of knowledge culture and knowledge sharing in organizations. Sharing knowledge culture in most reviewed publications is regarded as part of the overall organizational culture. The main role of the individuals in the process of creation of organizational knowledge is stressed by most authors cited in the article. Organizations cannot create knowledge without individuals, so they have to support creative individuals and to provide the context for knowledge generation. There is a great variety of factors influencing the creation and development of knowledge culture mentioned in the knowledge management literature. The tenfactor model proposed by Oliver Stan and Kondal Reddy Kandadi, based on their empirical analysis, is introduced. These factors are leadership, evangelization, infrastructure, physical attributes, reward systems, communities of practice, business process, recruitment, time allocation, organizational structure. The great role of the leadership in the development of knowledge culture is recognized. On the basis of theoretical analysis some conclusions are made.